BABY POTATOES-A NOVEL WAY OF POTATO CONSUMPTION - Luthra, Satish Kumar; Dalamu; VK Gupta; Vikas Mangal (Potato Journal, 2024)
In potato production, optimum tuber size is important to maximize crop value and hence growers target different tuber sizes at harvest to meet the localized market demand as produce size affects the pricing. Normally medium sized and large sized tubers get premium rates as compared to small tubers in the market, however, small sized tubers of specific varieties are also liked for some specific purposes and therefore get premium rates. In the changing food habit scenario, tubers weighing 20-40 grams specially packed and marketed as “baby potatoes” attract consumers. Baby potatoes are valued by consumers for freshness, taste, size and shape. Baby potatoes are consumed worldwide in a variety of dishes through various culinary methods.